Digital Service Platforms - Kang, Kyeong (IntechOpen, 2021)
E-service is an increasingly popular business practice and a critical part of supporting the global information society. The Digital Service Platforms book reduces the ambiguity about e-service by clarifying how to take advantage of it as well as how to overcome barriers and issues. It includes ten chapters in three subject areas: e-service and social media, e-service concepts, and e-service quality and development. Chapters cover such topics as organization-community relationships, systematic e-service innovation, social media ecosystems, accessibility experience design, Industry 4.0, public e-employment services in different countries, and more.